2019
DOI: 10.18203/2394-6040.ijcmph20195040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a maternal, neonatal and child health intervention package in a rural district of Pakistan: a quasi-experimental study

Abstract: Background: Pakistan is among the countries which have the highest maternal, neonatal and child mortality rates. Immediate efforts are required to enable Pakistan to achieve the health related sustainable development goals. The continuum of care interventions can substantially reduce the mortality burden, however local evidence to implement them is lacking in Pakistan. We implemented the maternal, neonatal and child health intervention package comprised of health facility strengthening, capacity building, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Despite improvements observed in the essential newborn care practices, the absolute percentage changes were minimal due to probably the ingrained cultural practices and timing of counseling the mothers in the rural community. Similar findings were reported from maternal and newborn health related interventions [ 37 , 48 , 51 , 59 61 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite improvements observed in the essential newborn care practices, the absolute percentage changes were minimal due to probably the ingrained cultural practices and timing of counseling the mothers in the rural community. Similar findings were reported from maternal and newborn health related interventions [ 37 , 48 , 51 , 59 61 ].…”
Section: Discussionsupporting
confidence: 87%
“…Studies showed that neonatal and maternal morbidity and mortality can be significantly reduced with basic and low cost interventions if managed appropriately and with high coverage of PNHV [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maternal mortality rate, neonatal mortality rate, and under five-year old child mortality rate for Pakistan are unsatisfactory (Alimohamadi et al, 2019 ; Habib et al, 2019 ). One of the reasons identified for the high mortality rates in developing regions is low levels of institutional deliveries with skilled providers (Randive et al, 2014 ; Yoseph et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results show significant gains in wide-ranging MCH outcomes including service delivery (double difference of 33.1% and 30.5% in skilled birth attendance and institutional deliveries, respectively). 27 …”
Section: Discussionmentioning
confidence: 99%
“…The results show significant gains in wide-ranging MCH outcomes including service delivery (double difference of 33.1% and 30.5% in skilled birth attendance and institutional deliveries, respectively). 27 The voucher and contracting schemes seem to have had some success in improving the management of MCH interventions, by showing effects that were not observed in the other NPPI districts. Earlier research has claimed that the social mobilisation strategy and provision of in Rawalpindi on a rotational basis.…”
Section: Bmj Global Healthmentioning
confidence: 98%